Legal Protection of Student Victims of Sexual Violence in Educational Settings: A Victimological and Child Protection Perspective - Nike Cahyaningrum; Marisa Kurnianingsih (Yustisia Tirtayasa : Jurnal Tugas Akhir, 2026)
Sexual violence against students in Indonesia is an escalating concern that highlights urgent gaps in effective legal protection. This study examines the implementation of legal protection for student victims in Jatisrono District and identifies key obstacles that hinder its effectiveness. Using an empirical legal method, data were collected through in depth interviews with law enforcement, educational authorities, child protection agencies, and civil society organizations. The findings show that despite the existence of comprehensive legal frameworks, particularly Law No. 12 of 2022 on Sexual Violence Crimes and Law No. 35 of 2014 on Child Protection, protection remains suboptimal. Structural and cultural barriers, including limited institutional capacity, low legal awareness, and weak inter agency coordination, significantly impede implementation. The novelty of this study lies in its victimological and child protection perspective within a semi rural educational context. It contributes by offering context sensitive policy recommendations to strengthen local legal protection mechanisms for student victims.